2019
DOI: 10.21203/rs.2.15523/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Residential Radon Exposure and Cigarette Smoking in Association with Lung Cancer: a Matched Case-control Study in Korea

Abstract: Background: Residential radon exposure and cigarette smoking are the two most important risk factors for lung cancer. The combined effects thereof were evaluated in a multi-center matched case-control study in South Korea.Methods: A total of 1,038 participants were included, comprising 519 non-small cell lung cancer cases and 519 age- and sex- matched community-based controls. Residential radon levels were measured for all participants. Multivariate logistic regression was used to calculate odds ratios (OR) fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…There is compelling evidence of a synergistic effect between radon and smoking in contributing to lung cancer development (64,65). Smokers in high radon risk areas are more likely to develop lung cancer than smokers in low radon exposure areas (66,67). Furthermore, (66) reported an 11% increase in lung cancer, with InRn increasing by 100 Bq m -3 .…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling evidence of a synergistic effect between radon and smoking in contributing to lung cancer development (64,65). Smokers in high radon risk areas are more likely to develop lung cancer than smokers in low radon exposure areas (66,67). Furthermore, (66) reported an 11% increase in lung cancer, with InRn increasing by 100 Bq m -3 .…”
Section: Discussionmentioning
confidence: 99%
“…The explanation can be supported by the calculation of environmental health risk analysis (EHRA) which predicts the estimated level of carcinogenic risk of a toxic agent can start from the duration of exposure of 30 years (residential / settlement) [26]. However, there is one research journal article that belongs to Park, et al (2020) [27], who explained that there was a significant relationship between Rn exposure and the risk of lung cancer with the duration of residence of the occupants of the house, which was > 2 years and the Rn concentration of 100 Bq/𝑚 3 . This study provides another fact that the duration of exposure to Rn in the house to cause a risk of lung cancer in residents, may occur in the range of > 2 years of stay with Rn concentrations that exceed the WHO reference limit of 100 Bq/𝑚 3 [27] .…”
Section: Duration/residence Years Of the Occupantsmentioning
confidence: 99%
“…Then followed by another type of lung cancer, namely Squamous Cell Carcinoma which is found in three research journal articles [13], [23], [24], and Small Cell Lung Cancer found in two research journal articles [21], [22]. One article journal explained the types of lung cancer cells due to exposure to Rn were found to be Non-Small Cell Lung Cancer with stage I-IIIA [27].…”
Section: Subtypes Of Lung Cancermentioning
confidence: 99%